Efficacy of continuous glucose monitoring for finding unusual causes of hyperglycemia: a clinical case - A.M. Urbanovych; F.V. Laniush (Mìžnarodnij Endokrinologìčnij Žurnal, 2024)
Diabetes is a chronic condition that requires constant blood glucose self-monitoring. The carbohydrate metabolism compensation is usually assessed by the level of glycated hemoglobin. But it does not always help reveal the true cause of poor glycemic control. The devices for continuous glucose monitoring allows to assess blood glucose level in real time and find unusual causes of hyper- and hypoglycemia. Achieving target glycemic levels is influenced by many factors: age of patients, duration of diabetes, eating habits and eating disorders, level of education, patient’s understanding of the diabetes course. One of the reasons for not reaching the target levels of glycemia can be hyperphagic eating disorders, such as night eating syndrome. According to the American Psychiatric Association classification, night eating syndrome belongs to the category of “Other specified eating disorders”. Diagnostic criteria in this syndrome include consumption of > 25 % of food from the daily diet after dinner or at least 2 cases per week of food consumption at night; awareness of these episodes; and at least 3 of the following: morning anorexia, uncontrollable desire to eat between dinner and sleep or at night, conviction that eating will help you fall asleep or return to sleep, insomnia and/or bad mood in the morning. The prevalence of night eating syndrome in the general population is 1.1 %, and in those who refer to metabolic surgery specialists, it is 2–20 %. The presence of night eating syndrome in diabetes adversely affects metabolic control and complicates the management of these patients, in particular, they have higher levels of HbA1c, blood pressure and body mass index compared to individuals without such eating disorder. In this case report, we describe a patient with poor glycemic control who used continuous glucose monitor and was diagnosed with night eating syndrome that helped change management and achieve normoglycemia in the evening and nighttime.